Harry Potter and the goblet of fire - Rowling, J. K.; GrandPré, Mary; Rowling, J. K. (London : Bloomsbury, 2004)
Fourteen-year-old Harry Potter joins the Weasleys at the Quidditch World Cup, then enters his fourth year at Hogwarts Academy where he is mysteriously entered in an unusual contest that challenges his wizarding skills, friendships and character amid signs that an old enemy may be returning.
"4"--Spine.
Sequel to: Harry Potter and the prisoner of Azkaban.
7.2
5-8.
5-8
Keywords: Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Juvenile fiction; Magic -- Juvenile fiction; Potter, Harry (Fictitious character) -- Juvenile fiction; Wizards -- Juvenile fiction; Fantasy; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Fiction; Magic -- Fiction; Potter, Harry (Fictitious character) -- Fiction; Schools -- Fiction; Wizards -- Fiction; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Fiction; Magic -- Fiction; Potter, Harry (Fictional character) -- Fiction; School stories; Wizards -- Fiction; England -- Juvenile fiction; England -- Fiction; England -- Fiction; Fantastic fiction; Fantastic fiction